Analisis curahan tenaga kerja pria dan wanita dalam usahatani hortikultura di lahan gambut - Melaelika, Anastasia; Fitrianti, Wanti (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Research was conducted to examine the contribution of male and female workers in horticultural farming on peatlands in Limbung and Madu Sari Villages, Sungai Raya District, Kubu Raya Regency. The aim of this research is to find out the characteristics of horticultural farmers on peatlands, find out the amount of labor men and women use in horticultural farming on peatlands and how big the difference is in the amount of labor between the two, and find out the distribution of men's and women's decision making in horticultural farming on peatlands . Regarding the use of plant varieties, types of fertilizer, specific uses, and marketing of agricultural products. Are men or women dominant in decision making activities? Determining the sample size uses a saturated sampling technique, that is, the total number of samples is taken. The sample in this study was the total number of farmers taken from two villages, namely Madu Sari and Limbung villages, namely 40 respondents. The data analysis method used is descriptive qualitative and quantitative. The research results show that the average time spent by male workers is 50.31 HOK/planting season or a proportion of 74.62%, while the average time spent by female workers is 17.11 HOK/season or around 25.38%. This shows that there is still a lack of female labor in horticultural farming. Women's involvement appears to be dominant only in post-harvest activities. Apart from that, based on the distribution of men's and women's decision making in determining plant varieties, use of fertilizer types, specific uses, and marketing of horticultural farming products, it appears that women's involvement is still very limited. Is privation in decision making still very dominant? This shows that there is a gender gap in decision making for productive activities.